EED-Targeted PROTACs Degrade EED, EZH2, and SUZ12 in the PRC2 Complex. Issue 1 (16th January 2020) - Hsu, Jessie Hao-Ru; Rasmusson, Timothy; Robinson, James; Pachl, Fiona; Read, Jon; Kawatkar, Sameer; O' Donovan, Daniel H.; Bagal, Sharan; Code, Erin; Rawlins, Philip; Argyrou, Argyrides; Tomlinson, Ronald; et al.
Summary: Deregulation of the PRC2 complex, comprised of the core subunits EZH2, SUZ12, and EED, drives aberrant hypermethylation of H3K27 and tumorigenicity of many cancers. Although inhibitors of EZH2 have shown promising clinical activity, preclinical data suggest that resistance can be acquired through secondary mutations in EZH2 that abrogate drug target engagement. To address these limitations, we have designed several hetero-bifunctional PROTACs (proteolysis-targeting chimera) to efficiently target EED for elimination. Our PROTACs bind to EED (pKD ∼ 9.0) and promote ternary complex formation with the E3 ubiquitin ligase. The PROTACs potently inhibit PRC2 enzyme activity (pIC50 ∼ 8.1) and induce rapid degradation of not only EED but also EZH2 and SUZ12 within the PRC2 complex. Furthermore, the PROTACs selectively inhibit proliferation of PRC2-dependent cancer cells (half maximal growth inhibition [GI50 ] = 49–58 nM). In summary, our data demonstrate a therapeutic modality to target PRC2-dependent cancer through a PROTAC-mediated degradation mechanism. Highlights: EED-targeted PROTACs bind to EED and promote ternary complex formation with VHL EED, EZH2, and SUZ12 are selectively degraded by EED-targeted PROTACs EED-targeted PROTACs reduce proliferation of EZH2-dependent cancer cells Abstract : Hsu et al. describe the discovery of EED-targeted PROTACs that lead to the degradation of multiple components of the PRC2 complex. Furthermore, they demonstrate that these PROTACs inhibit the proliferation of PRC2-dependent cancer cells and may be considered an attractive alternative to EZH2 catalytic inhibitors currently in clinical development.